Regulating effect of empagliflozin plus liraglutide on glucose/lipid metabolism and serum levels of SFRP5， Irisin and tAPN in obese type 2 diabetics - Gao Rui-chao; Li Min; Jin Peng-ran; Liu Xuan; Feng Xue; Tan Zeng-huan (Linchuang shenzangbing zazhi)
ObjectiveTo explore the effects of enpagliflozin plus liraglutide on glucose/lipid metabolism and regulating the serum levels of secreted frizzled-related protein 5 （SFRP5）， Irisin and total adiponectin （tAPN）.MethodsFrom March 2019 to March 2021， 116 obese T2DM patients were randomized into two groups of observation （n=58） and control （n=58）. Control group received liraglutide for 3 months while observation group had empagliflozin on the basis of control group for 3 months. At pre-treatment and 3 months post-treatment， two groups were compared regarding the parameters of weight loss ［weight， waist circumference （WC）， body mass index （BMI）］， glucose metabolism ［glycated hemoglobin （HbA1c）， fasting blood glucose （FPG）， 2 h postprandial blood glucose （2 hPG）］， lipid metabolism ［low-density lipoprotein cholesterol （LDL-C）， high-density lipoprotein cholesterol （HDL-C）， triglycerides （TG）， total cholesterol （TC）］， insulin sensitivity ［homeostasis model islet β cell function index （HOMA-β）， homeostasis model insulin resistance index （HOMA-IR）］， serum levels of SFRP5， Irisin and tAPN and occurrences of adverse reactions.ResultsAfter 3-month treatment， body weight ［（74.93±2.68） vs （78.21±3.47） kg］， WC ［（90.40±2.17） vs （93.28±2.53） cm］ ，BMI ［（26.57±0.94） vs （27.94±1.06） kg/m2］ ，HbA1c ［（6.03±0.59）% vs （6.76±0.68）%］， FPG ［（6.24±0.73） vs （6.97±0.95） mmol/L］， 2 hPG ［（8.06±1.25） vs （8.83±1.50） mmol/L］， LDL-C ［（2.27±0.21） vs （2.58±0.27） mmol/L］， TG ［（1.83±0.34） vs （2.20±0.48） mmol/L］， TC ［（5.36±0.42） vs （5.92±0.53） mmol/L］ and HOMA-IR （2.35±0.24 vs 2.69±0.31） were lower in observation group than those in control group（P<0.05）. And the serum levels of SFRP5， Irisin and tAPN were higher in control group than those in control group （P<0.05）； The incidence of adverse reactions was 17.24% in observation group versus 12.07% in control group. And the difference was not statistically significant （P>0.05）.ConclusionFor obese T2DM patients， enpagliflozin plus liraglutide may improve glucose/lipid metabolism and insulin sensitivity， boost serum levels of SFRP5， Irisin and tAPN and accelerate weight loss. The safety profile is decent.